Can you hear me? Playback experiment highlights detection range differences between commonly used PAM devices: C-POD, F-POD and SoundTrap - Nicole R. E. Todd; Ailbhe S. Kavanagh; Mark J. Jessopp; Willem Verboom; Emer Rogan (PLoS ONE, 2025)
Passive acoustic monitoring (PAM) is a valuable tool for monitoring acoustically active small cetaceans such as the harbour porpoise (Phocoena phocoena), with a range of devices commonly used across studies. However, to ensure comparability of findings, there is a need to compare the ability of devices to detect acoustic signals. Using a playback approach, we determined the detection probability and effective detection radius/area (EDR/EDA) for co-deployed C-POD (Cetacean POrpoise Detectors), F-POD (Full waveform capture POD) and SoundTrap acoustic monitoring devices. We conducted playbacks of harbour porpoise recordings across two transects at a range of distances from moored devices, while accounting for a range of variables likely to influence the detection probability of playbacks. Distance from the devices influenced the detection probability across all devices, and a significant difference between transects was also found for the C-POD, possibly due to different ambient noise conditions. The maximum detection distance of the playbacks for the SoundTrap and the F-POD was between 400 - 500m, and EDR was estimated at 297m (EDA 0.276 km2) and 241m (EDA 0.181 km2), respectively. The maximum detection distance for the C-POD was lower, at 300 - 400m, and an EDR of 220m (EDA 0.153 km2). A lower EDR was calculated for harbour porpoise buzzes compared to clicks across devices, due to lower source level of buzzes, suggesting that time spent foraging may be underestimated in PAM studies. The results highlight how detection ranges may differ across commonly used PAM devices, affecting comparability of detection rates across studies. EDR/EDA is an important prerequisite for PAM-derived density and abundance estimates. As such, understanding how devices differ is essential for comparing studies and appropriate planning of long-term acoustic monitoring projects, particularly where estimates of abundance are a key goal.